Kelimpahan dan Sebaran Horisontal Fitoplankton di Perairan Muara Sungai Kakap Kabupaten Kubu Raya - Irwan Lovadi, Susi Andriani, Tri Rima Setyawati (Universitas Tanjungpura, 2015)
Phytoplankton plays an important role in aquatic ecosystem as a primary producer. This study aims to determine the genera, abundance and horizontal distribution of phytoplankton and to measure the physical and chemical characteristics in the estuary of Kakap River. The study was carried out between December 2013 and May 2014. Phytoplankton samples were taken from five stasions that were determined based on the differences in the environmental conditions by Adaptive Cluster Sampling Method. The samples of phytoplankton were taken when the river water was in a tidal conditions by plankton net. The composition of phytoplankton found in estuary of Kakap River composed of 7 divisions, 7 classes and 42 genera. The highest phytoplankton abundance found at high tides were 42,825 ind/L and 35,769 ind/L respectively. The highest abundance phytoplankton was found from Bacillariophyceae (43,329 ind/L). Horizontal distribution of phytoplankton showed that the further away from the area of river basin, more abundance and more diverse of phytoplankton. Based on the value of Diversity Index (H’) (3.006 - 3.3489), Dominance Index (D) (0.0473 – 0.0613) and Evennes Index (E) (0.7118 – 0.8548), the estuary of Kakap River was in stable condition with high diversity. Characteristics of physial and chemical factors in the river were able to support the life of phytoplankton.